A genosensor for detection of HTLV-I based on photoluminescence quenching of fluorescent carbon dots in presence of iron magnetic nanoparticle-capped Au. Issue 1 (December 2018) - Zarei-Ghobadi, Mohadeseh; Mozhgani, Sayed-Hamidreza; Dashtestani, Fariba; Yadegari, Amir; Hakimian, Fatemeh; Norouzi, Mehdi; Ghourchian, Hedayatollah
Abstract Carbon dots and Fe3 O4 @Au were synthesized to develop a new biosensor to detect DNA target. We investigated the photoluminescence property of carbon dots (CDs) in the presence of Fe3 O4 -capped Au (Fe3 O4 @Au). Firstly, we designed two dedicated probes for unique long sequence region of human T-lymphotropic virus type 1 genome. One of the probes was covalently bound to the CDs. In the absence of target, CDs-probe was adsorbed on the surface of Fe3 O4 @Au through two possible mechanisms, leading to quenching the fluorescence emission of CDs. The fluorescence emission of CDs was recovered in the presence of target since double-stranded DNA cannot adsorb on the Fe3 O4 @Au. Also, Fe3 O4 @Au can adsorb the unhybridized oligonucleotides and improves the accuracy of detection. The specificity of the proposed biosensor was confirmed by BLAST search and assessed by exposing the biosensor to other virus targets. The experimental detection limit of the biosensor was below 10 nM with linear range from 10 to 320 nM.